2023
DOI: 10.1002/etc.5579
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gaseous and Particulate Phase Polycyclic Aromatic Hydrocarbons Emitted During Preharvest Burning of Sugar Cane in Different Regions of Kwa‐Zulu Natal, South Africa

Abstract: Biomass burning is a significant anthropogenic source of air pollution, including the preharvest burning of sugar cane. These burn events result in atmospheric emissions, including semivolatile organic compounds, that may have adverse impacts on air quality and human health on a local, regional, and even a global scale. Gaseous and particulate polycyclic aromatic hydrocarbon (PAH) emissions from various sugar cane burn events in the province of Kwa‐Zulu Natal in South Africa were simultaneously sampled using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…Furthermore, a mean concentration for total gas phase PAHs of 0.76 μg m –3 was found in the field samples. In comparison to our prior study by Geldenhuys et al, where the mean total gas phase concentration of PAHs in the field experiments using a different sampling method with small polydimethylsiloxane portable denuder devices was reported at 3.4 μg m –3 , the here presented analysis detected a lower total PAH content. Since this previous study revealed that 90% of the total PAHs were present in the gas phase rather than the particle phase, it is crucial to consider both the gas and particle phases to accurately account for gas–particle transformations occurring in the atmosphere.…”
Section: Resultscontrasting
confidence: 78%
See 4 more Smart Citations
“…Furthermore, a mean concentration for total gas phase PAHs of 0.76 μg m –3 was found in the field samples. In comparison to our prior study by Geldenhuys et al, where the mean total gas phase concentration of PAHs in the field experiments using a different sampling method with small polydimethylsiloxane portable denuder devices was reported at 3.4 μg m –3 , the here presented analysis detected a lower total PAH content. Since this previous study revealed that 90% of the total PAHs were present in the gas phase rather than the particle phase, it is crucial to consider both the gas and particle phases to accurately account for gas–particle transformations occurring in the atmosphere.…”
Section: Resultscontrasting
confidence: 78%
“…Moreover, previous results by Geldenhuys et al suggest that, in addition to differences in biomass composition and crop characteristics, the influence of the prevailing weather and combustion conditions on biomass combustion emissions and their gas–particle partitioning also play an important role in the emission profiles. In this respect, previous results showed clear differences in PAH emission profiles from one sugar cane burning event to another …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations